Teachers' Perception of Teaching English for Young Learners and the Implementation in Public Primary Schools in Jembrana Sub-District - Listyariyani, N.P.R. (Universitas Pendidikan Ganesha, 2018)
Teaching English for Young Learners has certain principles that need to be followed, while in fact its implementation in public primary schools does not seem to follow those principles. This research aimed at investigating teachers’ perception of teaching English for young learners and its implementation in public primary schools in Jembrana subdistrict. The research was also used to explore the problems which are encountered by teachers in teaching English in the classroom. This study involved 3 English teachers of Public Elementary Schools in Jembrana subdistrict. The data were collected through questionnaire, rating scales, observation sheets, and interviews guide. The research design was embedded mixed method design with qualitative dominant. The data were analyzed through descriptive qualitative. The results showed that teachers gave strongly positive perceptions about TEYL. Meanwhile, the activities which occurred in the learning process were mostly deal with the component of “Teaching Through Activities” with average range was 10.33. This range means that the component of teaching through activities was very highly implemented among the nine components. The other components were rarely evident during the observation. Based on the result of interview, the main problems which were encountered by the teachers are the difficulty to teach pronunciation to the students, limited learning sources, limited time for preparing lesson, and lack of various learning activities. Thus, this study suggests the government or other policy makers to provide English teachers with some kinds of professional development on practical guidance of TEYL and sufficient learning sources as well.